Effect of Fluctuating Temperature Regime on Psychrophilic Anaerobic Digestion of Nightsoil - Singh, Lokendra; Alam, S. I.; Ramana, K. V. (Defence Science Journal, 2013)
The effect of temperature fluctuation on anaerobic digestion of nightsoil using 10 °C adapted inoculum was studied. The digester was subjected to repeated temperature cycling of 10 °C and 30 °C. The total biogas, CH/sub 4/ and H/sub 2/S content, volatile fatty acids and microbial counts were compared with control digesters. No significant deleterious effect was noticed during initial temperature shock of one week. However, repeated exposures reduced the counts of hydrogenotrophic methanogens. There was no effect on the content of CH/sub 4/ and H/sub 2/S in the biogas.